Serum levels of high mobility group box‐1 protein (HMGB1) and soluble receptors of advanced glycation end‐products (RAGE) in depressed patients treated with electroconvulsive therapy - Hiromi Abe; Mami Okada‐Tsuchioka; Naoto Kajitani; Wataru Omori; Kei Itagaki; Chiyo Shibasaki; Shuken Boku; Tetsuaki Matsuhisa; Minoru Takebayashi (Wiley, 2023)
Abstract Aims High mobility group box‐1 (HMGB1) is one of the damage‐associated molecular patterns produced by stress and induces inflammatory responses mediated by receptors of advanced glycation end‐products (RAGE) on the cell surface. Meanwhile, soluble RAGE (sRAGE) exhibits an anti‐inflammatory effect by capturing HMGB1. Animal models have shown upregulation of HMGB1 and RAGE in the brain or blood, suggesting the involvement of these proteins in depression pathophysiology. However, there have been no reports using blood from depressed patients, nor ones focusing on HMGB1 and sRAGE changes associated with treatment and their relationship to depressive symptoms. Methods Serum HMGB1 and sRAGE concentrations were measured by enzyme‐linked immunosorbent assay in a group of patients with severe major depressive disorder (MDD) (11 males and 14 females) who required treatment with electroconvulsive therapy (ECT), and also in a group of 25 age‐ and gender‐matched healthy subjects. HMGB1 and sRAGE concentrations were also measured before and after a course of ECT. Depressive symptoms were assessed using the Hamilton Rating Scale for Depression (HAMD). Results There was no significant difference in HMGB1 and sRAGE concentrations in the MDD group compared to healthy subjects. Although ECT significantly improved depressive symptoms, there was no significant change in HMGB1 and sRAGE concentrations before and after treatment. There was also no significant correlation between HMGB1 and sRAGE concentrations and the HAMD total score or subitem scores. Conclusion There were no changes in HMGB1 and sRAGE in the peripheral blood of severely depressed patients, and concentrations had no relationship with symptoms or ECT.